Charge‐density analysis using multipolar atom and spherical charge models: 2‐methyl‐1, 3‐cyclopentanedione, a compound displaying a resonance‐assisted hydrogen bond. Issue 2 (4th March 2014) - Nassour, Ayoub; Kubicki, Maciej; Wright, Jonathan; Borowiak, Teresa; Dutkiewicz, Grzegorz; Lecomte, Claude; Jelsch, Christian
<x xml:space="preserve">Abstract</x> The experimental charge‐density distribution in 2‐methyl‐1, 3‐cyclopentanedione in the crystal state was analyzed by synchrotron X‐ray diffraction data collection at 0.33 Å resolution. The molecule in the crystal is in the enol form. The experimental electron density was refined using the Hansen–Coppens multipolar model and an alternative modeling, based on spherical atoms and additional charges on the covalent bonds and electron lone‐pair sites. The crystallographic refinements, charge‐density distributions, molecular electrostatic potentials, dipole moments and intermolecular interaction energies obtained from the different charge‐density models were compared. The experimental results are also compared with the theoretical charge densities using theoretical structure factors obtained from periodic quantum calculations at the B3LYP/6‐31G** level. A strong intermolecular O—H...O hydrogen bond connects molecules along the [001] direction. The deformation density maps show the resonance within the O=C—C=C—OH fragment and merged lone pair lobes on the hydroxyl O atom. This resonance is further confirmed by the analysis of charges and topology of the electron density.